(untitled) (Latakia University Journal -Biological Sciences Series, 2021)
The aim of the research is to study indicators of the economic efficiency of a photovoltaic station in the village of Metn Al-Sahel in Tartous Governorate with a capacity of (300) kilowatts, by collecting economic data related to fixed costs, which amounted to (248500) euros, As for the variable costs in (2019), they amounted to (9800) euros, equivalent to (4)% of the fixed costs, and the economic indicators of the photovoltaic station were calculated in light of these data, where the economic efficiency index reached (2.4), which is an excellent indicator. The profitability coefficient for invested capital is (33) %, which is much higher than the interest on capital that is specified in banks, whether local or international, and the project can recover its capital within (6.7) years, it is a relatively short time compared to the economic age of (25) years. The annual net profit amounted to (38480) euros, as for the cost of producing a kilowatt hour (0.02) euro.